Perspectives of the Local Communities on the Development of Trans-Papua Road Infrastructure - Zepnat Kambu; M. Yamin Jinca; M. Saleh Pallu; M. Isran Ramli (Salehan Institute of Higher Education, 2022)
Since the development of public and social infrastructure, such as road infrastructure, affects people's welfare, regional discrepancies in development are a key problem for Papua's infrastructure development. True, it's a top priority. When planning, executing, and overseeing road building, as it should be with the Trans-Papua route, public awareness and participation in the physical implementation of infrastructure development should be considered. The construction of the Trans-Papua Road drew a negative reaction and a huge amount of criticism from many social circles. A lack of community engagement in the development and implementation of the Trans-Papua Road project, as well as a public perception of ignorance, are accused of causing resistance and conflict. This research is an effort to understand better the awareness of specific communities, which may be used to design a participatory development strategy. The study's focus is on how the public views the Trans-Papua road's development from sociocultural, economic, and environmental viewpoints. The data was gathered through a survey and complemented with statistics from the local Central Statistics Bureau. The results showed that the community and stakeholders have different perspectives and understandings of the Trans-Papua road's construction, and it has been determined that the community should be involved in the planning and implementation of development measures based on the response of the local. This study demonstrates the importance of reducing community-government conflicts, especially those involving protected forest conservation, community empowerment, and transportation network development. The findings of this study can be used to provide recommendations for infrastructure development, particularly in locations where native communities are at threat of conflict. Doi: 10.28991/CEJ-2022-08-05-011 Full Text: PDF